SERVICE QUALITY AND BRAND IMAGE EFFECTS ON CUSTOMER LOYALTY THROUGH SATISFACTION AT BINTANG MULYA INDAH - Irfan Miftahul Fauzi; Santosa Pradana Putra Setya Negara; Dian Ardifah Iswari; Ihwan Susila (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2026)
PURPOSE - This study seeks to examine the impact of service quality and brand image on customer loyalty, with customer satisfaction serving as a mediating variable among patrons of Bintang Mulya Indah General Merchandise Store in Madiun City.  The annual rise in the number of customers was the main reason for this study. It shows how important service quality, brand image, and customer satisfaction are for building customer loyalty.METHODOLOGY - This research utilizes a quantitative methodology with an explanatory research framework.  The population comprises all customers of Bintang Mulya Indah, while the sample was obtained through a non-probability accidental sampling method.  The Slovin formula was used to get 75 responses.  Data were gathered via observation, interviews, documentation, and Likert-scale questionnaires.  The analysis of the data included tests for validity and reliability, tests for normality, path analysis, t-tests, and Sobel tests to look at direct and indirect effects between variables.FINDING - The results indicate that: (1) service quality and brand image significantly enhance customer satisfaction; (2) service quality, brand image, and customer satisfaction substantially affect customer loyalty; (3) customer satisfaction serves as a mediator in the relationship between service quality and customer loyalty; and (4) customer satisfaction also acts as a mediator in the relationship between brand image and customer loyalty.